The complete mitochondrial genome of the oceanic squid: Chiroteuthis picteti (Oegopsida, Chiroteuthidae). Issue 1 (2nd January 2018) - Kim, Hana; Yu, Cheol; Kim, Hyung June; Kang, Dong Won; Jung, Yun-Hwan
Abstract: The mitogenome sequence of Chiroteuthis picteti Joubin, 1894 (Oegopsida, Chiroteuthidae), a species of Oceanic squid, was first determined in the genus Chiroteuthis as well as in the family Chiroteuthidae. The circular genome of C. picteti is 20, 851bp in size, has six duplicated genes ( cox1, cox2, cox3, atp6, atp8, and tRNA Asp ). The mitogenome of C. picteti has high A + T content (71.6%) similar to other Oegopsid (A 38.2%; C 18.3%; G 10.1%; T 33.4%). The mitogenome of C. picteti, the first reported of its genus, will be useful for inferring the phylogenetic relationships among the members of Chiroteuthidae, within the Oegopsids.